A joint experimental and theoretical study on the structural, electronic and optical properties of malayaite and Chromium‐doped malayaite structures as pigments. (June 2020) - Vaselnia, S.Y.; Aminian, M. Khajeh; Motahari, H.; Banadaki, R. Dehghan
Abstract: Ceramic pigments due to their properties of thermal stability and suitable optical characteristics are widely used in industries. Hence, the theoretical study of pigments based on density functional theory (DFT) is valuable to predict the structural, electronic, optical and especially colorimetric properties of them. We have synthesized the malayaite (CaSnSiO5 ) and chromium-doped malayaite with variable chromium concentration by the conventional ceramic route. Also, we have modeled these structures and performed DFT/TDDFT calculations by using the Quantum ESPRESSO package and YAMBO code. We studied the structural, electronic and optical properties of the structures. The role of chromium in the malayaite structure is determined by Energy Dispersive Spectroscopy (EDS), X-ray diffraction (XRD) and Raman spectroscopy methods. For the Cr-doped samples, it is shown that main XRD and Raman peaks have been shifted and it has explained the reason for the resonance-enhancement of vibrational modes of the samples. In the electronic property calculations, it is indicated that the gap and Fermi energies of the theoretical samples with increasing the doping concentration are decreased. In the optical properties section, UV–Vis spectroscopy and CIE L*a*b* colorimetry methods are used and the correspondence of the absorption spectra and colorimetric results for all samples is shown. Also, the gap energy of the experimental samples is compared to the theoretical samples. The results indicate the advantage of the DFT method for ceramic pigments. Graphical abstract: Image 1 Highlights: Synthesis of the malayaite and Cr-doped malayaite by the conventional ceramic route. DFT/TDDFT calculations of the structures by the Quantum ESPRESSO and YAMBO code. Shift of the XRD and Raman peaks and resonance-enhancement of vibrational modes for doped samples. Decrease of the gap and Fermi energies with increasing the doping concentration. Checking the correspondence of the absorption spectra and colorimetric results for all samples.